Assessing the Impact of COVID-19-1 on Small-Scale Enterprises in Uganda: A Case Study of Kasokoso Trading Centre in Kira Municipality, Wakiso District. - Hannah E Rwothuwinjo (Uganda Christian University, 2023)
This study was primarily intended to highlight the difficulties faced by small scale businesses during and after the extensive corona virus pandemic, which had an impact on all sectors and was felt globally. However, the study will be primarily focused on small scale enterprises in the nation of Uganda. The study employed the use of secondary data for the literature review and mainly focused on data that dated not more than five years prior to the study. And for the field research the researcher used primary data analysis which involved feedback from respondents from the chosen population and this was in accordance with a descriptive research design as its methodology. In addition, both qualitative and quantitative research methods were used to perform this study. The outcome of the secondary data analysis demonstrates that both small and large businesses are facing difficulties, and that the unprecedented coronavirus crisis has destroyed many companies around the world hence most of the businesses both globally and locally are facing similar problems when it comes to the effects of covid 19 pandemic which has made it difficult for these businesses survive with some effects like decreased revenue, lost jobs, slowed-down life, and poor marketing performance. The study was able to identify some key areas in the operations of SSEs that were affected by the pandemic and also was able to draw conclusions on how these areas where affected by covid 19 pandemic i.e. the key area that was identified and that cut across for all businesses that belong to the category of SSEs was the businesses saving nature. Under the businesses saving nature the researcher further more researched about of the ways in which covid 19 has affected SSEs saving abilities and also the nature of saving as well as the different solutions that can be used by the different stake holders in order to soothe on the implications of these effects.
This is a dissertation.